Peranan Serasah Terhadap Sumbangan N dan P pada Agroekosistem Kopi - RUSDI EVIZAL; TOHARI TOHARI; IRFAN D. PRIJAMBADA; JAKA WIDADA (Fakultas Pertanian Universitas Udayana, 2012)
Litter is the main source of organic matter and nutrient entrance in shade grown coffee agroecosystems.Shade trees provide ecological and economic benefits in coffee agro-ecosystems thatindicate the key factor for sustainable coffee production. This study examined the role of litter onnutrient (N and P) returning in coffee agro-ecosystems. The experimental plots of Coffea canephorawere constucted at benchmark site of Conservation and Sustainable Management of Below-GroundBiodiversity (CSM-BGBD), in Sumberjaya Subdistrict, West Lampung, Indonesia, during 2007-2010.Types of shade trees to be examined were legume shade trees of Gliricidae sepium and Erythrinasububrams, non-legume tree of Michelia champaca, and no shade tree. The results showed that: (1)kind of shading determined litter productivity of coffee agro-ecosystems. Litter productivity of coffeeagro-ecosystems with shade trees increased coffee bean yield, (2) litter was an important source of Nand P that returned into the soil. Amount of nitrogen from litter biomass has linier effect on coffee beanyield.